SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT PADA EVENT ORGANIZER (STUDI KASUS: PT BINTANG ABADITAMA - Maharani Anindya Salsabila, (2023)
Currently, there are more and more companies engaged in services, one of which is an event organizer company. PT Bintang Abaditama is one of the companies in Jakarta engaged in event organizers that has been running for more than 10 years. Problems that occur in the marketing process caused by the lack of promotional media to get customers and problems in managing customer data. Customers are very important in companies in the field of services because companies in this field require prolonged service to customers. To overcome this, a Customer Relationship Management (CRM) strategy that focuses on how to maintain good relationships with customers, can help companies in dealing with existing problems. The creation of a website-based CRM system uses the SDLC approach method with a waterfall model as a work flow.